HEALTHY LIFESTYLE: SOCIAL REPRESENTATION OF TYPE 2 DIABETES MELLITUS PATIENTS - QUEIROZ, NÊDA LYAN SOUTO LOPES DE; tavares, paula paulina costa; SILVA, NELIA DE OLIVEIRA DAMASCENO DA; DAMASCENO, MARCIA OLIVEIRA; ABDALA, GINA ANDRADE; MEIRA, MARIA DYRCE DIAS (International Journal of Research -GRANTHAALAYAH, 2020)
Objective: to identify the social representations of type 2 Diabetes Mellitus patients on the effect of an educational intervention to guide the adoption of healthy habits. Method: This was a qualitive study, where semi-structured intervies. Semi-structured interviews were applied after an educational intervention and were analized using the Collective Subject Discourse technique, based on the Theory of Social Representations. Results: 21 patients participated. In the analysis of the three questions, eleven Central Ideas emerged: “Aspects that contribute to health”; "There are difficulties for putting it into practice"; "Everything positive, including the attention received"; "It is possible, everything is there in nature"; "It is possible, but it does not replace the drugs"; "It is not always possible, it depends on some factors"; “If the person doesn’t want it, everything is difficult”; “You can use them all”; “Mainly sun, physical activity, healthy eating ”; "I like water very much"; “Trust in God is essential”. Final considerations: the participants recognized the importance of adopting a healthy lifestyle and highlighted the positive results of adopting healthy habits.